The generation of CD25+ CD4+ regulatory T cells that prevent allograft rejection does not compromise immunity to a viral pathogen. - Bushell, A; Jones, E; Gallimore, A; Wood, K (2005)
In all but a small minority of cases, continued survival of solid organ grafts after transplantation depends on lifelong, nonselective immunosuppression that, although effective, results in increased rates of infection, cancer, and vascular disease. Therapeutic strategies that engage or mimic self-tolerance may allow prolonged allograft survival without the disadvantages of nonspecific immunotherapy. Pretreatment of recipient mice with donor alloantigen combined with transient modulation of the peripheral T cell pool with anti-CD4 Ab leads to the indefinite survival of MHC-incompatible cardiac allografts without further therapy. Tolerance is dependent on CD25+ CD4+ regulatory T cells that arise from naive CD25- precursors and regulate rejection via both IL-10 and CTLA-4. Although these cells are clearly effective at controlling rejection, the proven ability of recently activated CD25+ cells to mediate bystander regulation raises the possibility that tolerized individuals might also have a reduced capacity to respond to environmental pathogens. We have examined anti-influenza responses in tolerized primary heart recipients, secondary recipients following adoptive transfer of regulatory populations, and tolerized mice in which bystander regulation has been deliberately induced. Neither virus-specific CTL activity in vitro nor the clearance of virus in vivo was significantly diminished in any of these treatment groups compared with infected unmanipulated controls. The data suggest that the induction of dominant allograft tolerance dependent on regulatory T cells does not necessarily result in attenuated responses to pathogens providing further support for the development of tolerance induction protocols in clinical transplantation.